2019
DOI: 10.1148/rg.2019190064
|View full text |Cite
|
Sign up to set email alerts
|

MRI of the Male Pelvic Floor

Abstract: The pelvic floor is a complex structure that supports the pelvic organs and provides resting tone and voluntary control of the urethral and anal sphincters. Dysfunction of or injury to the pelvic floor can lead to gastrointestinal, urinary, and sexual dysfunction. The prevalence of pelvic floor disorders is much lower in men than in women, and because of this, the majority of the published literature pertaining to MRI of the pelvic floor is oriented toward evaluation of the female pelvic floor. The male pelvic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 58 publications
0
15
0
Order By: Relevance
“…Although males and females can present with the same PFS, key anatomical, hormonal, neuromuscular, and behavioral differences exist that result in sex and gender differences in those symptoms 21–23 . We found that more females than males reported pelvic pain.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Although males and females can present with the same PFS, key anatomical, hormonal, neuromuscular, and behavioral differences exist that result in sex and gender differences in those symptoms 21–23 . We found that more females than males reported pelvic pain.…”
Section: Discussionmentioning
confidence: 69%
“…Although males and females can present with the same PFS, key anatomical, hormonal, neuromuscular, and behavioral differences exist that result in sex and gender differences in those symptoms. [21][22][23] We found that more females than males reported pelvic pain. This finding is well known in the literature and may be explained by differences in the neuroimmune system or how sex hormones influence nociceptive systems.…”
Section: Discussionmentioning
confidence: 78%
“…The organ prolapse of each chamber can be visually observed and quantitatively analyzed by pelvic floor ultrasound, which provides detailed pelvic floor morphological and functional information for clinical practice, and is beneficial to identify the type of prolapse. Based on the above advantages, ultrasound is widely used in the diagnosis of pelvic floor diseases [ 18 , 19 ]. However, with the deepening of people's understanding of diseases, people's requirements for the quality of ultrasonic images are also improving.…”
Section: Discussionmentioning
confidence: 99%
“…MRI relies on its own advantages of high resolution of soft tissues, capable of multi-parameter imaging and no ionizing radiation, comprehensively assessing the structure and function of the pelvic floor, and has become the imaging gold standard for evaluating the structure and function of the pelvic floor. However, the cost of MRI examination is high, the examination time is long, and the pelvic floor can't be assessed (36). Ultrasound has attracted more and more attention in the diagnosis of pelvic floor dysfunction diseases because of its unique advantages such as simple operation, real-time and fast, economical non-invasive, repeatable examination, and high resolution of soft tissues (37).…”
Section: Discussionmentioning
confidence: 99%